The Living Tradition of Living in the Law: Paul’s Use of Leviticus 18:5 (Indonesian Journal of Theology, 2016)
This essay addresses Paul’s quotations of Leviticus 18:5 in Galatians and Romans. Starting from the interpretive tradition of Leviticus 18:5, intertextuality between the quotation and the surrounding texts is traced along with echoes of Leviticus 18:5 throughout each epistle. It is demonstrated that Paul interpreted Leviticus 18:5 in Galatians in connection to the reward of life. In Romans, on the other hand, Paul interpreted Leviticus 18:5 as the law written on the hearts of those who are in Christ –thus fulfilling its covenantal function. Rather than implying inconsistency, Paul’s different applications of Leviticus 18:5 are consistent with the unity of his view on the law.